Analisa Kadar Tembaga (Cu) Air Mertojoyo Mengguakan AAS (Atomic Absorbtion Spectrofotometry) Berdasarkan Permenkes Tahun 2010 - Atiqoh, Siti Nor (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Heavy metal contamination from the processing industry and waste treatment is very detrimental to health because it is carcinogenic. One of the heavy metals which are harmful is copper (Cu). Cu content analysis aims to determine the type of water that is decent and not decent to drink based on the content of Cu according to the Regulation of Health Minister in 2010. The method was used is anexperimental sample by used the random water samples on Mertojoyo, Sigura-Gura, Malang. Cu content analysis is using AAS (Atomic Absorption Spectrofotometry) with standard solution for comparison Cu. From the analysis results obtained equation y = 0,15x + 0.004 of the standard curve and absorb y = 0.0002 in order to obtain the concentration of Cu in water samples Sigura-Gura Mertojoyo area with the manual calculation of -0.024204 mg / L and by AAS 0,001 mg / L. The levels are still below the maximum level is specified by the Minister of Health ynag 492 / Minister of Health / per / IV / 2010 in 2010 with the maximum levels of Cu in water sebsar 2 mg / L. So the water on SiguraGura Mertojoyo area is stated feasible for use of the standard the existence of Cu. Cemaran logam berat hasil dari pengolahan industri dan pengolahan limbah sangat merugikan terhadap kesehatan karena bersifat karsinogenik. salah satu logam berat yang termasuk berbahaya ialah tembaga (Cu). Analisa kadar Cu bertujuan untuk menentukan jenis air yang layak dan tidak layak minum berdasarkan kandungan Cu menurut Permenkes tahun 2010. Metode yang digunakan ialah experimental sampel dengan mengambil sampel air secara acak daerah Mertojoyo Sigura-gura Malang. Analisa kadar Cu menggunakan AAS (Atomic Absorbtion Spectrofotometry) dengan larutan standar cu sebagai pembanding. Dari hasil analisa didapatkan persamaan y=0,15x+0,004 dari kurva standar dan absorbi y= 0,0002 sehingga diperoleh konsentrasi Cu dalam sampel air daerah Mertojoyo Sigura-gura dengan perhitungan manual sebesar -0,024204 mg/L dan dengan AAS sebesar 0,001 mg/L. Kadar tersebut masih dibawah kadar maksimal ynag dietapkan oleh permenkesNo.492/menkes/per/IV/2010 tahun 2010 dengan kadar maksimal Cu dalam air sebsar 2 mg/L. Sehingga air mertojoyo sigura-gura dinyatakn layak untuk digunakan dari standar keberadaan Cu.